THE EFFECTS OF SINGING IN ENGLISH ON THE SPEECH FLUENCY OF TURKISH TEENAGERS LEARNING ENGLISH AS A FOREIGN LANGUAGE - Esim Gürsoy; Ozan Karakaş (Informascope, 2018)
Singing has been suggested to have a positive influence on the speech fluency of people with various neurological disorders, such as stuttering, aphasia, and autism. Again, research demonstrates the benefits of singing as a teaching method, through which many aspects of language can be taught or improved, such as grammar, vocabulary, pronunciation. However, there are not any studies as to the effects of singing on the speech fluency of people with no neurological speech disorders. Thus the study aims at investigating any possible influences of singing on the speech fluency of Turkish EFL teenagers. The study was carried out with 10 high-school students (control n=6, experimental n=4) studying at a private school in Turkey. The quantitative data was collected via a questionnaire that aimed to identify the demographic features of the participants. To identify the utterance fluency, audio recordings of the participants' speech production were collected. The speech samples were produced subsequent to watching short film clips after the participants in the study group were given two songs each week for 5 weeks. The results of the study demonstrate that none of the three measures of fluency showed any significant differences between or within the groups, suggesting that singing does not necessarily have positive influences on speech fluency.